2023
DOI: 10.1038/s41598-023-45745-5
|View full text |Cite
|
Sign up to set email alerts
|

A multi-objective optimization design approach of large mining planetary gear reducer

Wen Xin,
Yanyan Zhang,
Yang Fu
et al.

Abstract: A two-stage computational framework is proposed to optimize the radiated noise and weight of a large mining planetary gear reducer under the rated conditions, based on a combination of response surface methodology and multi-objective optimization. The well-established transient dynamic analysis model of a large mining planetary gear reducer, which is used to analyze the mechanical strength and acoustic characteristics of the gear reducer. A unified experimental design is developed to obtain the response surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Constants related to the battery were modeled using data applied in real vehicles as shown in Table 8. Equations ( 6) and (7) present the simple modeling of the battery to calculate voltage and SOC. The charging and discharging currents of the battery were calculated by multiplying the power required by the motor by the efficiency of the motor.…”
Section: Modeling Of Longitudinal Vehicle Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constants related to the battery were modeled using data applied in real vehicles as shown in Table 8. Equations ( 6) and (7) present the simple modeling of the battery to calculate voltage and SOC. The charging and discharging currents of the battery were calculated by multiplying the power required by the motor by the efficiency of the motor.…”
Section: Modeling Of Longitudinal Vehicle Dynamicsmentioning
confidence: 99%
“…In line with this trend, extensive research and development have been conducted on motors, inverters, reducers, etc. resulting in significant improvements in power and efficiency [7,8]. Particularly, there is a considerable focus on efficiency studies related to motors and inverters [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the bearing alignments could be effective on the system vibrations due to the bearing constraint reinforcement. Xin et al [23] proposed a dynamic model of a PGS for a mining reducer. They optimized the gear parameters to enhance the acoustic vibration performances of the system.…”
Section: Kinematic Modeling Of the Drpgsmentioning
confidence: 99%